PENGARUH MEKANISME KOPING TERHADAP KECEMASAN PASIEN KANKER PAYUDARA DI RUMAH SAKIT GRANDMED LUBUK PAKAM TAHUN 2020 - Tati Murni Karokaro; Winardi Silaen; Abdi Lestari Sitepu; Dian Anggriyanti (JURNAL KEPERAWATAN DAN FISIOTERAPI (JKF), 2020)
The success of the mechanism of coping in patients with cancer is breast does not only depend on the detection since the early , but also of understanding will be the mechanism causes . One of the conditions that can cause anxiety is the process of carrying out chemotherapy treatment . The purpose of this study was to determine the effect of the mechanism coping against the anxiety of cancer breast at home Sick Grandmed Lubuk Pakam . Type penel itian is using methods quasy Experiment with using the design study One-group pretest-posttest design. The determination of the samples is done by way of purposive sampling, with the number of samples seban yak 30 people . Analysis of the data is done by using a test Paired Sample T Test with a confidence interval of 95% and the value of Î± = 0.05. The results were obtained from studies have demonstrated the presence of changes in the level of anxiety of patients before and after a given application of the mechanism of coping with value p-value = 0.001 (Î±> 0.05). Conclusion , there is the influence of the mechanisms of coping against the anxiety of patients kankker breasts were conducted in accordance with the standard, For Institutions Health need for supervision and counseling to the public that the importance of maintaining health , especially in patients with cancer of breast in Rs. Grand Lubuk Pakam